2008
DOI: 10.4012/dmj.27.835
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a new jet nozzle for removal of carious dentin with an air abrasion system

Abstract: A new version of an air abrasion device, which expelled abrasive sodium bicarbonate powder, was fabricated to remove carious tissue. This device had a motor-driven mechanism to control the amount of powder expelled. The purpose of this study was to estimate the abrading efficacy of this device, in particular the new jet nozzle, for removal of carious dentin. Powder was supplied to the handpiece by a rotary gear attached to the powder control motor. Two types of jet nozzles, a cylinder-type and a bugle-type, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…As an alternative to conventional mechanical techniques such as steel round burs or hand excavators, which uses impact pressure for caries removal, the air abrasion technique has been introduced. Honda et al 17) in particular, visually evaluated removal of carious dentin using the cylinder-type nozzle and two sizes of the bugle-type nozzle (0.6-1.0 nozzle and 0.8-1.2 nozzle) each on four teeth, and showed that the bugletype nozzles were favorable for the removal of carious dentin. However, air abrasion cannot be used for all patients, such as in cases of severe dust allergy, asthma, chronic obstructive lung disease, recent extraction or other oral surgery, open wounds, advanced periodontal disease, recent placement of orthodontic appliances and oral abrasions, or subgingival caries removal 18) .…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to conventional mechanical techniques such as steel round burs or hand excavators, which uses impact pressure for caries removal, the air abrasion technique has been introduced. Honda et al 17) in particular, visually evaluated removal of carious dentin using the cylinder-type nozzle and two sizes of the bugle-type nozzle (0.6-1.0 nozzle and 0.8-1.2 nozzle) each on four teeth, and showed that the bugletype nozzles were favorable for the removal of carious dentin. However, air abrasion cannot be used for all patients, such as in cases of severe dust allergy, asthma, chronic obstructive lung disease, recent extraction or other oral surgery, open wounds, advanced periodontal disease, recent placement of orthodontic appliances and oral abrasions, or subgingival caries removal 18) .…”
Section: Discussionmentioning
confidence: 99%